Design and Research on Vehicle Axle Box Inboard Bogie Exported to Malaysia - Ti XIAO; Shizhong HE; Gongan TAO; Huixia LIU; Qi ZHANG; Tao LI (机车电传动)
The advantages of the vehicle axle box inboard bogie were introduced, and the main technical parameters of the vehicle axle box inboard bogie exported to Malaysia were provided. The technical characteristics, structural characteristics and wheelset forces of the bogie were analyzed. Compared with the bogie outside the axle box, the weight of the bogie with built-in axle box was reduced by about 20% and the unsprung mass was reduced by about 30%, which had obvious lightweight advantages. Under the same vehicle load conditions, the axle load reduction rate calculation result showed that the axle box inboard bogie improved axle load reduction rate about 50% in air spring inflation and deflation cases, which improved the running safety.